Effect of acidulant addition on yogurt fermentation - Karen A. Schmidt (Kansas Agricultural Experiment Station Research Reports, 2009)
Yogurt was manufactured by pre-acidifying the yogurt mix with citric acid, lactic acid, or concentrated lemon juice either before or after pasteurization to a target pH of 6.2, and then the traditional manufacturing process was continued. Adding citric acid or lemon juice to the yogurt mix after pasteurization resulted in a 13% reduction in fermentation time compared with the control. This reduction in fermentation time may result in greater efficiency for yogurt manufacturers, allowing for a more sustainable manufacturing process.; Dairy Day, 2009, Kansas State University, Manhattan, KS, 2009; Dairy Research, 2009 is known as Dairy Day, 2009
Keywords: Kansas Agricultural Experiment Station contribution; no. 10-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1021; Dairy Day; 2009; Dairy; Dairy processing; Citric acid; Lemon juice; Yogurt